Attention Span of Children With Mild Intellectual Disability: Does Music Therapy and Pictorial Illustration Play Any Significant Role? - Jacob, Udeme Samuel; Pillay, Jace; Oyefeso, Esther Olufunke (Frontiers in Psychology, 2021)
This study investigated the effects of music therapy and pictorial illustration on the attention span of children with mild intellectual difficulties. A pre-test, post-test and control group quasi-experimental research design was used with a sample of children diagnosed with mild intellectual disability from three special schools in Ibadan, Nigeria. Fifty children were randomly selected and assigned to one of three groups: music therapy, pictorial illustration, or control (N = 50, male = 25, female = 25, mean age = 11.6 years). Twenty-four sessions of music therapy and pictorial illustration classes were held with the experimental group only. The Moss Attention Rating Scale was used before and after the intervention to collect data on participants’ attention span. Analysis of Covariance indicated that there was a significant statistical difference between pre-test and post-test results of the two groups. The estimated marginal means of post-attention span by treatment indicated that pictorial illustration had the highest post-attention span score, followed by music therapy, while post-attention span score for the control group was the least. Based on the findings, it is recommended that teachers, caregivers, and parents of children with mild intellectual disability adopt pictorial illustration and music therapy as teaching strategies to enhance their attention span.